AKTIVITAS ANTI-Staphylococcal SECARA IN VITRO EKSTRAK DIKLOROMETANA DARI RIMPANG TEMU KUNCI (Boesenbergia rotunda) TERHADAP Staphylococcus aureus ATCC 25923 - Matutu, Deni Ari; Hairani, Rita; Ruga, Ritbey (JURNAL ATOMIK, 2025)
The rhizome of temu kunci (Boesenbergia rotunda) is one of the plants used by the local people in Indonesia as a traditional medicine. This study aimed to identify the secondary metabolite compounds contained in the dichloromethane extract with phytochemical screening and investigate its antibacterial activity against test bacteria Staphylococcus aureus ATTC 25923 was carried out by agar diffusion method with modification where tetracycline as a positive control and ethanol as a negative control. The phytochemical screening showed the dichloromethane extract contains secondary metabolites such as alkaloids, flavonoids, phenolics and triterpenoids. With 1 mg/mL of dichloromethane extract revealed its antibacterial activity against S. aureus with inhibitory zone value of 15.0 ± 0.0 mm while its MIC value of the extract was 0.031 ± 0.0 mg/mL toward of tested bacteria. In addition, tetracycline as a positive control at 0.5 μg/mL exhibited its antibacterial potential with an inhibitory zone value of 22.0 ± 0.0 mm and its MIC value of 0.016 ± 0.577 µg/mL.